Biomechanical Strategies Underlying the Robust Body Armour of an Aposematic Weevil - Wang, Lu-Yi; Rajabi, Hamed; Ghoroubi, Nima; Lin, Chung-Ping; Gorb, Stanislav N. (Frontiers in Physiology, 2018)
Robust body armour is one of many anti-predator strategies used among animal taxa. The exoskeleton of insects can serve as the secondary defence mechanism in combination with the primary defense such as warning colour. Aposematic Pachyrhynchus weevils advertise their unprofitability and use their robust exoskeleton for effective defence against lizard predators. While the mature weevils survive after the predatory attack, the soft teneral ones can easily be consumed. To reveal how the mature weevils achieve such effective protection, we investigated the ontogenetic changes in the microstructure and material properties of the exoskeleton of the adult weevils. We also tested the functional role of a weevil-specific structure, the fibrous ridge, in the robustness of the elytral cuticle of the mature weevils. The results showed that the mature weevils have thicker, stiffer and more sclerotized cuticle than the teneral ones. The fibrous ridges in the endocuticle considerably increase the overall stiffness of their cuticle. Together these biomechanical strategies enable Pachyrhynchus weevils to achieve robust body armour that efficiently protects them from lizard predation.